2020
DOI: 10.1186/s12889-020-09599-0
|View full text |Cite
|
Sign up to set email alerts
|

Geospatial patterns of comorbidity prevalence among people with osteoarthritis in Alberta Canada

Abstract: Background Knowledge of geospatial pattern in comorbidities prevalence is critical to an understanding of the local health needs among people with osteoarthritis (OA). It provides valuable information for targeting optimal OA treatment and management at the local level. However, there is, at present, limited evidence about the geospatial pattern of comorbidity prevalence in Alberta, Canada. Methods Five administrative health datasets were linked to identify OA cases and comorbidities using validated case def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Furthermore, the size of 132 LGAs varies greatly across the province. The average size of 31 metro LGAs in Calgary and Edmonton is 50 km 2 compared to the average size of 26,742 km 2 in the 12 rural remote LGAs in the north zone [ 3 ]. As urban areas have a larger number of PCP options available within a highly populated, smaller geographic area, urban patients usually have reasonable access to PCPs across many LGAs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the size of 132 LGAs varies greatly across the province. The average size of 31 metro LGAs in Calgary and Edmonton is 50 km 2 compared to the average size of 26,742 km 2 in the 12 rural remote LGAs in the north zone [ 3 ]. As urban areas have a larger number of PCP options available within a highly populated, smaller geographic area, urban patients usually have reasonable access to PCPs across many LGAs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the advantage of using LGA, an administrative geographic unit, as the area unit for analysis is that it aligns with the planning purposes of AHS, which uses LGA to monitor, plan, and evaluate the delivery of health services in Alberta. The sizes of LGAs vary greatly across rural and urban areas, ranging from 7 km 2 in the metro areas to 99,994 km 2 in the rural remote areas [ 3 ]. This may bring in bias when measuring travel time and cross-boundary travel patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Health inequalities are common in rural and northern regions of Alberta, particularly in terms of adequate access to preventive and primary healthcare [50,58]. Rural communities with greater distances to large urban centers often have lower vaccination rates than their metropolitan counterparts [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…Given that both influenza and several upper and lower respiratory tract infections in children are preventable through vaccinations, this may result in higher rates in ED visits and hospitalizations in these regions. Several studies have also shown that rural and northern communities face barriers to accessing primary care [58,63,64]. They often require ED visits as their only means of obtaining healthcare services or may require these services due to the progressive severity of their conditions [65].…”
Section: Discussionmentioning
confidence: 99%